2022
DOI: 10.1021/acs.langmuir.1c03319
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Antibacterial Ability and Bioactivity of Polyetherketoneketone Modified with LL-37

Abstract: Polyetherketoneketone (PEKK) is considered to be a potential substitute material for metal bone implants because of its advantageous biocompatibility, chemical stability, and mechanical properties, but clinical application has been severely restricted due to PEKK's lack of antibacterial ability and biological activity. In this study, LL-37, a natural human antimicrobial peptide, was successfully modified on the PEKK surface with polydopamine as the intermediate layer and released continuously for more than 6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…The cells were collected and used between passages 3 and 5. The culture medium was refreshed every 2–3 days 29 …”
Section: Methodsmentioning
confidence: 99%
“…The cells were collected and used between passages 3 and 5. The culture medium was refreshed every 2–3 days 29 …”
Section: Methodsmentioning
confidence: 99%
“…The light absorption values were measured at 490 nm after the dimethyl sulfoxide was dissolved. [ 9b,43 ] Formazan accumulation was proportional to the number of viable cells. [ 9b,43b ] Strains TH and TH‐103Z were cultivated in LB medium or fermentation medium at 37 °C.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, AMPs have highly selective toxicity to bacterial cell membranes and are not easy to damage mammalian cells ( Xi et al, 2016 ; Zhang et al, 2021 ). Recently, many studies have confirmed that AMPs could improve the antibacterial properties of biological materials ( Pranantyo et al, 2016 , 2018 , 2019 , 2021 ; Albada and Metzler-Nolte, 2017 ; Yang et al, 2017 ; Cao et al, 2018 ; Zhang et al, 2020 ; Wang H. et al, 2021 ; Yan et al, 2021 ; Jin et al, 2022 ). HHC36 (KRWWKWWRR) is a highly effective AMP containing nine amino acids predicted and designed by the artificial neural network.…”
Section: Introductionmentioning
confidence: 99%